Unveiling new degradation intermediates/pathways from the photocatalytic degradation of microcystin-lr - Shoemaker, Jody A.; De La Cruz, Armah A.; Antoniou, Maria G. (My University, 2008)
Mass spectrometry was utilized for structural identification ofthe intermediates formed during the photocatalytic degradation of the cyanotoxin, microcystin-LR with immobilized TiO2 photocatalysts at neutral pH. Most of the intermediates reported herein have not been found in prior studies. Results indicate that MC-LR degradation is initiated at four sites of the toxin; three on the Adda amino acid (aromatic ring, methoxy group, and conjugated double bonds) and one on the cyclic structure (Mdha amino acid). Several intermediates gave multiple peaks in the TIC (m/z = 1011.5, 1029.5, 1063.5), which were deduced to be geometrical or constitutional isomers. This is the first study that reports the hydroxylation of the aromatic ring and the demethoxylation of MC-LR with TiO2 photocatalysis. The most targeted site was the conjugated diene bonds because of their location in the MC-LR structure. Isomerization at the C4-C5 and C 6-C7 of the diene bond of the Adda chain was a direct result of hydroxyl radical addition/substitution. Based on the above, we concluded that oxidation and isomerization of the diene bonds of MC-LR occurred simultaneously. Other steps included hydroxyl substitution, further oxidation, and bond cleavage. As the reaction time progressed, simultaneous oxidation of the Adda chain and the cyclic structure occurred.
Keywords: Microcystins; Aromatic compounds; Isomerization; Photodegradation; Oxidation; Mass spectrometry